The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5194/se-8-291-2017
|View full text |Cite
|
Sign up to set email alerts
|

Deformation in cemented mudrock (Callovo–Oxfordian Clay) by microcracking, granular flow and phyllosilicate plasticity: insights from triaxial deformation, broad ion beam polishing and scanning electron microscopy

Abstract: Abstract. The macroscopic description of deformation and fluid flow in mudrocks can be improved by a better understanding of microphysical deformation mechanisms. Here we use a combination of scanning electron microscopy (SEM) and broad ion beam (BIB) polishing to study the evolution of microstructure in samples of triaxially deformed Callovo-Oxfordian Clay. Digital image correlation (DIC) was used to measure strain field in the samples and as a guide to select regions of interest in the sample for BIB-SEM ana… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 87 publications
0
49
1
Order By: Relevance
“…Therein, gouge injection occurs into less pressurized host rock fractures where the gouge-bounding micrometer-thin shear zone failed. Contrary to rather brittle, i.e., spontaneous, localized failure of the OPA in common laboratory experiments, the in situ gouge fabric suggests a long-term creep behavior and distributed shear along micrometer-thin shear zones (see "dry" experiments in Giger et al, 2008;Desbois et al, 2017), where fluid flow is drastically inhibited perpendicular to shear, but temporarily enhanced parallel to shear inside the gouge. In direct shear experiments, Bakker et al (2017) showed for synthetic OPA gouges that a clay-enriched gouge has a lower friction coefficient than gouge with an unaltered OPA composition.…”
Section: Physical Rock Properties Of Gougementioning
confidence: 79%
“…Therein, gouge injection occurs into less pressurized host rock fractures where the gouge-bounding micrometer-thin shear zone failed. Contrary to rather brittle, i.e., spontaneous, localized failure of the OPA in common laboratory experiments, the in situ gouge fabric suggests a long-term creep behavior and distributed shear along micrometer-thin shear zones (see "dry" experiments in Giger et al, 2008;Desbois et al, 2017), where fluid flow is drastically inhibited perpendicular to shear, but temporarily enhanced parallel to shear inside the gouge. In direct shear experiments, Bakker et al (2017) showed for synthetic OPA gouges that a clay-enriched gouge has a lower friction coefficient than gouge with an unaltered OPA composition.…”
Section: Physical Rock Properties Of Gougementioning
confidence: 79%
“…Imaging grain-scale deformation microstructures (at sub-micrometre scale) in clay-rich geomaterials is challenging because such materials are difficult to prepare with conventional methods without intensive damage to microfabrics. Microstructural studies are nevertheless required to fully understand the bulk rheology of these materials (Morgenstern and Tchalenko, 1967;Logan et al, 1979, Lupini et al, 1981Rutter et al, 1986;Logan et al, 1992;Saffer and Marone, 2003;Dehandschutter et al, 2004, Dehandschutter et al, 2005aDehandschutter et al, 2005b;Colletini et al, 2009;Haines et al, 2009;Haines et al, 2013;Kaufhold et al, 2016;Desbois et al, 2017a). Ion beam methods (FIB: Focussed Ion Beam; BIB: Broad Ion Beam) enable the preparation of high-quality cross sections and, in combination with scanning-electron microscopy (SEM), currently pave the way to new fields of qualitative and quantitative investigations of phyllosilicate-rich geomaterials (Desbois et al, 2009;Milliken & Reed, 2010;Heath, 2011;Klaver et al, 2012;Hemes et al, 2013;Houben et al, 2013;Desbois et al, 2014;Houben et al, 2014;Laurich et al, 2014;Warr et al, 2014;Hemes et al, 2015;Klaver et al 2015;Hemes et al, 2016;Laurich et al, 2017;Laurich et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ion beam methods (FIB: Focussed Ion Beam; BIB: Broad Ion Beam) enable the preparation of high-quality cross sections and, in combination with scanning-electron microscopy (SEM), currently pave the way to new fields of qualitative and quantitative investigations of phyllosilicate-rich geomaterials (Desbois et al, 2009;Milliken & Reed, 2010;Heath, 2011;Klaver et al, 2012;Hemes et al, 2013;Houben et al, 2013;Desbois et al, 2014;Houben et al, 2014;Laurich et al, 2014;Warr et al, 2014;Hemes et al, 2015;Klaver et al 2015;Hemes et al, 2016;Laurich et al, 2017;Laurich et al, 2018). This approach allows investigating deformed phyllosilicate-rich geomaterials at nanometre-resolution with unprecedented clarity (Laurich et al, 2014;Desbois et al, 2017a;Laurich et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…even concluded that amorphous silica was not found in the OPA and that neoformed quartz cement formed during diagenesis is well preserved with un-corroded crystal planes. The mineral assemblage of amorphous material and clays is typical in several gouge localities, although in more mature fault gouges (Power and Tullis, 1989;Di Toro et al, 2004;Hadizadeh et al, 2012;Janssen et al, 2013;Kirkpatrick et al, 2013;Kameda et al, 2017). Figure 15.…”
Section: Diffusive Mass Transport (Pressure Solution Precipitation Anmentioning
confidence: 99%